Physical properties and color stability of injection-molded thermoplastic denture base resins - Song, So-Yeon (J Adv Prosthodont, 2019)
PURPOSE: The purpose of this study was to compare mechanical and physical properties of injection-molded thermoplastic denture base resins. MATERIALS AND METHODS: In this study, six commercially available products (VA; Valplast, LC; Lucitone, ST; Smiltone, ES; Estheshot-Bright, AC; Acrytone, WE; Weldenz) were selected from four types of thermoplastic denture base materials (Polyamide, Polyester, Acrylic resin and Polypropylene). The flexural properties and shore D hardness have been investigated and water sorption and solubility, and color stability have evaluated. RESULTS: For the flexural modulus value, ES showed the highest value and WE showed significantly lower value than all other groups (P<.05). Most of experimental groups showed weak color stability beyond the clinically acceptable range. CONCLUSION: Within the limits of this study, thermoplastic denture base resin did not show sufficient modulus to function as a denture base. In addition, all resins showed discoloration with clinical significance, and especially polyamides showed the lowest color stability.